Omalizumab for the treatment of chronic spontaneous urticaria: association between body mass index and outcome - Irene Russo; Sara Cazzolla; Francesca Pampaloni; Mauro Alaibac (Mattioli1885, 2022)
Introduction: Omalizumab has been recently registered as a third-line therapy for chronic spontaneous urticaria. Objectives: In this study, we aimed to provide real life data by reporting our experience with omalizumab in the treatment of chronic spontaneous urticaria. Methods: A retrospective data analysis was conducted on 40 patients affected by chronic spontaneous urticaria and treated with omalizumab at the Dermatology Unit of University of Padua, Italy.Demographic, anthropometric, and clinical data have been collected. Results: Overall, the majority of patients (23 patients, 57.5%) achieved complete recovery by taking omalizumab and 17.5% (7 patients) had a partial response. The majority of patients who did not have a response to omalizumab had a BMI> 25 kg/m2. Conclusions: Our study suggests that omalizumab is a safe and effective treatment for chronic spontaneous urticaria. We identified BMI as a critical biological factor that significantly impacts the outcomes of omalizumab treatment. Our findings also suggest a potential use of BMI as a predictive biomarker for omalizumab treatment. An updosing of omalizumab may be proposed in patients with high BMI to achieve a better control of the disease.